2019
DOI: 10.3389/fneur.2019.00979
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Algorithm to Identify Predictors of Treatment Response: Tapentadol Monotherapy or Tapentadol/Pregabalin Combination Therapy in Chronic Low Back Pain?

Abstract: Purpose: High dose monotherapies or drug combinations are used to achieve sufficient analgesia for the treatment of severe chronic low back pain, before invasive therapy options are considered. In order to demonstrate an alternative for an empirical treatment approach, the authors' primary aim was to present an algorithm for the objective identification of treatment predictors. Additionally, the study identified baseline-characteristics in chronic low back pain patients prior to tapentadol PR treatment, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…With regards to the combination of tapentadol with other analgesics, the paper by Otto et al on low back pain [72] and that by Lockwood and Dickenson on osteoarthritis [44], both published in 2019, demonstrated the useful combination of tapentadol and pregabalin.…”
Section: Chronic Back Painmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to the combination of tapentadol with other analgesics, the paper by Otto et al on low back pain [72] and that by Lockwood and Dickenson on osteoarthritis [44], both published in 2019, demonstrated the useful combination of tapentadol and pregabalin.…”
Section: Chronic Back Painmentioning
confidence: 99%
“…glutamate release). A recent study conducted in LBP patients suggests that the combination therapy (tapentadol PR + pregabalin) exerts its best clinical efficacy in subjects characterized by severe sleep disturbances and little anxiety [72]. Moreover, a study by D'Amato et al showed the efficacy of the combination of tapentadol and ketoprofen after hip arthroplasty [73].…”
Section: Chronic Back Painmentioning
confidence: 99%
“…Retrospective subgrouping of patients (ie, “responders” vs “nonresponders”) has been suggested as an elegant statistical method for identifying factors contributing to a treatment response. 25 Accordingly, we retrospectively classified our patients into “responders” and “nonresponders” but unfortunately failed to identify neither objective nor patient-reported baseline characteristics that may predict treatment success (except for catastrophizing). This somewhat contradicts the finding of another cannabis cohort, which was able to point predictors for good response (≥30% decrease in average pain intensity) including normal to long sleep duration, lower BMI, lower depression scores, and a diagnosis other than neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Post hoc prediction models of treatment efficacy were performed incorporating different outcome parameters. A retrospective analysis of a study comparing the efficacy of tapentadol versus tapentadol plus pregabalin in chronic low back pain identified predictive parameter combinations for response to median doses of tapentadol [41]: low baseline pain intensity, good sleep quality and high PD-score.…”
Section: Nonpain Patient-reported Outcome Measuresmentioning
confidence: 99%